Understanding and Managing Staff Development in an Urban School System. Final Report - Schlechty, Phillip ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1983)
A study is reported that examined the way staff development functions in schools, the effects of staff development, and the interaction between staff development and other activities and conditions in school systems. The study took place in a large urban school district (in the Southeast) that is heavily committed to and involved in staff development. Following descriptions and discussions of: (1) how power and authority are distributed in the system; (2) the functions of staff development and the motivations of participants; and (3) the capacity of staff development programs to maintain direction, maintain coordination, and exercise control over resources, two related arguments are advanced: (1) the way schools are presently organized places considerable pressure on the staff development enterprise to keep things from getting worse and distracts attention from the intended purpose of staff development, which is to make things better, and (2) until the maintenance system of schools (i.e., the system that keeps things from getting worse) is considerably enriched, there is little likelihood that change-oriented staff development can systematically succeed. On the basis of the descriptive material and the analysis, some concrete suggestions are made regarding how staff development might be improved. Appended are materials relating to the initial research questions, program selection criteria, descriptions of the programs studied, and recommendations made by the researchers on the question of merit pay. (CMG)
Sponsoring Agency: National Inst. of Education (ED), Washington, DC.
Contract Number: 400-79-0056.
Educational level discussed: Elementary Secondary Education.
Teachers.
Practitioners.
May also be available online. Address as at 14/8/18
Keywords: Coordination; Educational Cooperation; Educational Improvement; Elementary Secondary Education; Incentives; Program Design; Program Effectiveness; Program Evaluation; Program Implementation; Research Methodology; Staff Development; Teacher Motivation; Urban Education; Reports, Research